Enhanced pH sensitivity over the Nernst limit of electrolyte gated a-IGZO thin film transistor using branched polyethylenimine. Issue 13 (26th January 2016) - Kumar, Narendra; Kumar, Jitendra; Panda, Siddhartha
Abstract : a-IGZO based EGTFT with 4.6-fold enhanced pH sensitivity of ∼110 mV pH −1 using thin film coating of branched polyethylenimine (BPEI). Abstract : This paper reports the use of branched polyethylenimine (BPEI) coated amorphous indium gallium zinc oxide (a-IGZO) based electrolyte gated thin film transistors (EGTFTs) to obtain a pH sensitivity of ∼110 mV pH −1 which is above the Nernst limit. The a-IGZO, used both as the active layer and pH sensitive layer, obviates the need of a separate high-K dielectric thereby simplifying the process of fabrication of TFT based sensors along with their operation at a low voltage range (−2 V to 2 V). Two EGTFT devices, one with bare a-IGZO and the other with BPEI coated a-IGZO were utilized in this work. The electrical double layer (EDL) formation at the a-IGZO/electrolyte interface was studied with the capacitance–voltage analysis which showed well defined accumulation and depletion regimes at a small voltage range (−1 V to 1 V) with the EDL capacitance of ∼2.0 μF cm −2 . The EGTFT with bare a-IGZO film showed a good I ON / I OFF ratio of the order of ∼10 3, a sub-threshold swing of 238 mV dec −1, and saturation mobility of 3.0 cm 2 V −1 s −1 but a pH sensitivity of 24 mV pH −1 . The utilization of BPEI with this structure, reported for the first time, resulted in ∼4.6 fold enhancement in the sensitivity. The BPEI layer enhances the pH sensitivity and could also facilitate the use of such devices for biosensing as the amine groups of the BPEI could be used as linkers for immobilizing biomolecules for capturing target analytes. The device structure used in the work is compatible for fabrication on flexible substrates which enable lower cost and applications needing form factor.